Analysis of Principal Managerial Skills in State Senior High Schools - Vivit Erisa; Hilal Mahmud; St. Marwiyah; Edhy Rustan (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
This study aims to analyze the implementation of the principal managerial skills, internal and external factors that contribute, and their impact on improving the quality of education in state senior high schools in Palopo, Indonesia. This research is field research using the mixed method approach. Data was obtained through questionnaires, interviews, observation, and documentation studies. The mapping of school positions was analyzed using the IFE (Internal Factors Evaluation) matrix and EFE (External Factors Evaluation) matrix. The study results show that the principals implement managerial skills, namely conceptual, interpersonal, and technical skills, to improve education quality. The results of the analysis of the internal (Strengths and weaknesses) and external factors (Opportunities and Threats) evaluation show that the strengths possessed by each school can overcome its weaknesses and are very responsive in overcoming threats in improving the quality of education. The implementation of principal managerial skills has a positive impact on improving the quality of education.